(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2016)
The present study was carried out in Pedro Franco Dávila Scientific Station (Palenque parish, province of Los Ríos). The aim was to evaluate the status of conservation of chiropterofauna in the remaining semideciduous forest. At night, mist nets were displayed at soil and subcanopy levels, sampling 1533 h/web, from May to August 2015; meanwhile during the day, bat refugia were searched. Abundance-range and species accumulation curves were elaborated, Shannon-Wiener and Pielou evenness diversity index were calculated; additionally, the threatened categories of the species were reviewed. A total of 46 individuals, belonging to 10 species, 7 genera and 2 families were captured. Sturnira bakeri (29%) is dominant, followed by Desmodus rotundus and Glossophaga soricina with 15% each, respectively. Saccopteryx bilineata was found on a tree of Ficus sp. (Moraceae). The trophic guilds that were recognized are: frugivorous, omnivorous, hematophagous and insectivorous. Diversity numbers (H’= 1.98; J’=0.86), indicate a medium diversity. Sturnira bakeri, Glossophaga soricina, Carollia brevicauda and Saccopteryx bilineata are new records for the scientific station.